The Development of Political Institutions Power, Legitimacy, Democracy - Ferrari, Federico (Weiser Center for Emerging Democracies, 2022)
While the literature on "new institutionalism" explains the stability of institutional arrangements within countries and the divergence of paths of institutional development between countries, Federico Ferrara takes a "historical institutionalist" approach to theorize dynamic processes of institutional reproduction, institutional decay, and institutional change in explaining the development of political institutions. Ferrara synthesizes "power-based" or "power-distributional" explanations and "ideas-based" "legitimation explanations." He specifies the psychological "microfoundations" of processes of institutional development, drawing heavily from the findings of experimental psychology to ensure that the explanation is grounded in clear and realistic assumptions regarding human motivation, cognition, and behavior. Aside from being of interest to scholars and graduate students in political science and other social-scientific disciplines whose research concentrates on the genesis of political institutions, their evolution over time, and their impact on the stability of political order and the quality of governance, the book will be required reading in graduate courses and seminars in comparative politics where the study of institutions and their development ranks among the subfield's most important subjects.